1999
DOI: 10.1046/j.1432-1327.1999.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of human elastase inhibitors from a conformationally constrained combinatorial peptide library

Abstract: A resin-bound cyclic peptide library was constructed based on the sequence of the reactive-site loop of Bowman±Birk inhibitor, a proteinase inhibitor protein. The constrained loop sequence, which incorporates the minimal proteinase-binding motif, was retained throughout the library, but selected residues known to be important for inhibitor specificity were randomised. The approach was used to create a`one bead, one peptide' library with 8000 variants resulting from randomization at three target locations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 71 publications
3
41
0
Order By: Relevance
“…At the bottom of the S1 pocket, the respective residue (Ser 189 in PPE or Gly 189 in HNE) is inaccessible to the P1 side chain of the inhibitor, as it is covered by the hydrophobic parts of Ile 138 and Thr 226 (in PPE) or Val 190 (in HNE). Compared with PPE, the S1 pocket of HNE shows an increased flexibility, enabling the adaptation to a broader variety of P1 side chains (11,23 elastase inhibitory activity determined for wild-type rShPI-1A and for BPTI (18), both of which contain Lys at position P1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the bottom of the S1 pocket, the respective residue (Ser 189 in PPE or Gly 189 in HNE) is inaccessible to the P1 side chain of the inhibitor, as it is covered by the hydrophobic parts of Ile 138 and Thr 226 (in PPE) or Val 190 (in HNE). Compared with PPE, the S1 pocket of HNE shows an increased flexibility, enabling the adaptation to a broader variety of P1 side chains (11,23 elastase inhibitory activity determined for wild-type rShPI-1A and for BPTI (18), both of which contain Lys at position P1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the interaction with PPE is usually very weak or not observed at all (18,21). This elastase specificity could be attributed to a more flexible S1 pocket in HNE that allows accommodation of a broad variety of P1 residues (11,(22)(23)(24). Supporting this concept, the substitution at P1 position with amino acids characterized by medium-sized hydrophobic side chains, such as Val, Ala, and Leu, not only increases the affinity of BPTI for HNE (25)(26)(27) but also converts it into a tight-binding inhibitor of pancreatic elastase with K i values around 10 Ϫ9 M. Affinity selection of a phage-displayed library of BPTI variants against PPE reveals an almost exclusive preference for Leu at the P1 position (28).…”
mentioning
confidence: 99%
“…It therefore seems reasonable to suggest that the SmCI-D1 (domain 1, containing such threonine) could contribute to a lesser extent to inhibiting trypsin and be responsible for elastase inhibition. The additional presence of a hydrophobic residue at P2Ј, able to interact with the S2Ј subsite of the enzyme, could favor elastase inhibition (74) by this first SmCI domain. The inhibition of pancreatic elastase by the rSmCI D1-D2 and its lack by the rSmCI D2-D3 indicates that the D1 domain is probably responsible for the inhibition of this enzyme, also suggesting an important role of the P1 threonine residue in this event.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Screening of this P 4 , P 1 , and P 2 Ј bead library against human leukocyte elastase (HLE) has also been described 49 (Table IX). A total of 23 active binding beads were analyzed in this study, with 21 of these being found to have Ala at P 1 and the remaining two Thr.…”
Section: Figurementioning
confidence: 99%